Efeito da administração oral de precursores hepáticos de glicose na recuperação da glicemia em camundongos submetidos à hipoglicemia induzida pela insulina - Santiago, Amanda Nunes (2012)
We previously demonstrated that the ability of the liver to produce glucose from alanine, glutamine, lactate and glycerol during insulin-induced hypoglycemia (IIH) was increased in adult male Wistar rats. In this investigation we expanded this line of research to adult male Swiss mouse. All animals were submitted to 14 h fasting before the experiments. In the first set of experiments the effect of increasing doses of intraperitoneal Regular insulin (0,0 U/kg, 0,1U/Kg, 0,5 U/kg, 1,0 U/kg, 1,5 U/kg, 2,0 U/kg) on blood glucose levels were evaluated. Blood samples were collected 0, 30, 60, 90, 120, 150, 180, 240 and 300 min after insulin injection. Because the group that received Regular insulin 1,0 U/kg showed a clear glucose recovery phase without convulsions or deaths, this dose was adopted in the following experiments. Thus, these experiments were repeated again and 15 min after the administration of Regular insulin (1,0 U/kg) the animals received by gavage: saline (control group), glucose (100 mg/Kg), glycerol (100 mg/Kg), lactate (100 mg/Kg), alanine (100 mg/Kg), glutamine (100 mg/Kg), glutamine (50 mg/Kg) + alanine (50 mg/Kg) or glycerol (50 mg/Kg) + lactate (50 mg/Kg). The animals which received oral alanine or glutamine showed best glucose recovery and glutamine was superior to alanine. Since the spontaneous recovery of blood glucose begins 3 h after the intraperitoneal injection of insulin (1 UI/Kg), this time was chosen for the in situ liver perfusion experiments where the liver glucose production from increasing concentrations of alanine, glutamine, lactate or glycerol were investigated. In part of the experiments the liver production of lactate, pyruvate and urea were determined. To glycerol the higher liver glucose production of IIH group did not reach significant statistical values. In addition, the glucose production from higher concentrations of lactate was lower (p<0.05) in the IIH group. On the other hand IIH increased (p <0.05) the capacity of the liver to produce glucose from glutamine and alanine. Taken together the results demonstrated that the best performance of oral alanine and glutamine on glucose recovery could be attributed, partly at least, to the fact that livers from mice submitted to IIH showed increased ability to produce glucose from alanine and glutamine in comparison with normoglycemic group.